Diagnosing Intraductal Papillary Mucinous Neoplasm of the Bile Duct with Computed Tomography: A Clinical Case Analysis - Xinzheng WANG; Jinzhi FANG; Dafei YU; Jianbing ZENG; Yuzhong ZHANG; Linning E (CT Lilun yu yingyong yanjiu)
Objective: This study aimed to explore the computed tomography (CT) features of the intraductal papillary mucinous neoplasm of the bile duct (IPMN-B). Methods: A retrospective analysis was conducted on the clinical data and CT findings of three patients with surgically and pathologically confirmed IPMN-B. Additionally, a review of the relevant literature was performed. Results: All three IPMN-B cases exhibited well-defined circular cystic lesions on CT cans. These lesions contained solid mural nodules or soft tissue densities with visible pedicles within the cysts. Notably, the lesions connected to the bile duct, and surrounding bile ducts showed varying degrees of dilation. Enhanced CT scans revealed mild to moderate uneven enhancement within the solid components of all three lesions, while the cystic components displayed no enhancement. Interestingly, one patient with IPMN-B underwent follow-up examinations over four years, demonstrating gradual enlargement and malignant transformation of the lesion. None of the three cases showed lymph node enlargement around the liver or retroperitoneum. Conclusion: The study suggests characteristic CT features of IPMN-B. These include well-defined cystic lesions with accompanying solid wall nodules or masses. Additionally, most lesions connect to the bile duct and are accompanied by bile duct dilation.